Knowledge of aflatoxins contamination in peanut-based products among food handlers: retailers' perspective - Mohd Azaman, Nur Nazurah; Kamarulzaman, Nitty Hirawaty; Shamsudin, Mad Nasir; Selamat, Jinap (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
The occurrence of aflatoxins contaminants in foods has been reported widely. Unfortunately, only a few know about the effects and risk from aflatoxins contamination to human health. Knowledge of the danger of aflatoxins contamination in peanuts-based products is still lacking among food handlers. Thus, this study was undertaken with the aim of determining the knowledge of aflatoxins contamination in peanut-based products among retailers. Data were collected from 128 retailers in Klang Valley area. Face-to-face interviews were conducted by using semi-structured questionnaires. The result indicated that the household size, income level, and experience in retail showed significantly association with knowledge about aflatoxins contamination in peanut-based products. Thus, this study suggest that there is a need for public awareness campaigns regarding aflatoxins contamination as to improve the knowledge and awareness of public about the dangers of aflatoxins to health.